ANALISIS PEMANFAATAN SCREENCAST O MATIC DALAM PEMBERDAYAAN KETERAMPILAN KOMUNIKASI LISAN MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS TIMOR - Sele, Yunawati; Oetpah, Fincensius (LPPM Institut Pendidikan Nusantara Global, 2023)
This research was conducted with the aim of obtaining an overview of the use of Screencast O Matic in empowering oral communication skills of students of the Biology Education study program, University of Timor. This research is quantitative descriptive. The research subjects were students of the Biology Education Study Program at the University of Timor who programmed the Teaching and Learning course. The instrument used is an open questionnaire containing five questions. The collected data were analyzed using descriptive statistics. The results showed that empowering the oral communication skills of students of the Biology Education study program at the University of Timor could not be carried out optimally. The reason is the low readiness and awareness of students to take part in new lecture patterns, including lectures based on Screencast O Matic.